Organic pineapple farming in Ghana: A good choice for smallholders? - Linda Kleemann (Kiel Institute for the World Economy (IfW), 2011)
As consumer demand for organic food grows, organic certification is increasingly promoted in many developing countries. Organic products earn a premium price on the market compared to conventional varieties. Hence, organic production is often seen as a valuable alternative for developing countries with many smallholders. Using value chain analysis for the case of the pineapple sector in Ghana and extensive data from the European market, this paper tries to shed light on the feasibility and profitability of organic small-scale production. Even though smallholders tend to have quality problems with their fruit and large farms benefit from economies of scale, production for the export market is a realistic option for both organic and conventional smallholders. The results indicate that organic production is more profitable for smallholders than conventional production and farmers collect a fair share of the price premium on the retail level. Even more, from a theoretical perspective, organic farmers should also be more likely to get into contractual relations with exporters. The results are set into perspective with relation to the debates on small versus large farms, environmental impact, and the selection effect of standards.
Keywords: F14; L11; L15; O13; Q13; Q17; 330; Private voluntary standards; organic agriculture; trade in organic products; GLOBALGAP; value chain analysis; Ökologischer Landbau; Obstbau; Landwirtschaftlicher Kleinbetrieb; Betriebliche Wertschöpfung; Rentabilität; Fruchthandel; Exporthandel; Ghana